Effect of moderate- or high-intensity inspiratory muscle strength training on maximal inspiratory mouth pressure and swimming performance in highly trained competitive swimmers - Ohya, T.; Kusanagi, K.; Koizumi, J.; Ando, R.; Katayama, K.; Suzuki, Y. (International Journal of Sports Physiology and Performance, 2022)
Purpose: Inspiratory muscle strength training (IMST) can improve exercise performance. Increased maximal inspiratory mouth pressure (MIP) could be beneficial for swimmers to enhance their performance. This study aimed to clarify the effect of high-intensity IMST for 6 weeks on MIP and swimming performance in highly trained competitive swimmers.